Synthesis, Characterization and Antibacterial Activity of Novel Coumarin - Zhang1, Tian-Lin; Ma1, Hui-Min; Zhu1, Cai-Yan; Wang1, Jia-Jia; Wang3, Bing-Bing (Asian Journal of Chemistry, 2013)
The novel coumarin derivative based quaternary ammonium salt had been designed and synthesized in two steps starting from 5-chloromethylsalicylaldehyde. 5-Chloromethylsalicylaldehyde first reacted with tertiary amine to yield the quaternary ammonium salt, then this compound reacted with the diethyl malonate on the appropriate condition to yield the corresponding coumarin derivative. The chemical structure had been elucidated by infrared spectra, 1H NMR spectra, LC-MS and melting point analysis. The novel coumarin had been evaluated for its antibacterial activities in vitro against foru gram-negative bacteria (Edwardsiella tarda, Aeromonas hydrophila, Vibrio anguillarum and Vibrio harveyi). The bioactive assay showed that the title compound displayed comparable antibacterial efficacy in comparison with some of other reference drugs.